Transcatheter versus surgical aortic valve replacement in lower-risk and higher-risk patients: a meta-analysis of randomized trials. (20th January 2023) - Ahmad, Yousif; Howard, James P; Arnold, Ahran D; Madhavan, Mahesh V; Cook, Christopher M; Alu, Maria; Mack, Michael J; Reardon, Michael J; Thourani, Vinod H; Kapadia, Samir; Thyregod, Hans Gustav Hørsted; Sondergaard, Lars; et al.
Abstract: Aims: Additional randomized clinical trial (RCT) data comparing transcatheter aortic valve implantation (TAVI) with surgical aortic valve replacement (SAVR) is available, including longer term follow-up. A meta-analysis comparing TAVI to SAVR was performed. A pragmatic risk classification was applied, partitioning lower-risk and higher-risk patients. Methods and results: The main endpoints were death, strokes, and the composite of death or disabling stroke, occurring at 1 year (early) or after 1 year (later). A random-effects meta-analysis was performed. Eight RCTs with 8698 patients were included. In lower-risk patients, at 1 year, the risk of death was lower after TAVI compared with SAVR [relative risk (RR) 0.67; 95% confidence interval (CI) 0.47 to 0.96, P = 0.031], as was death or disabling stroke (RR 0.68; 95% CI 0.50 to 0.92, P = 0.014). There were no differences in strokes. After 1 year, in lower-risk patients, there were no significant differences in all main outcomes. In higher-risk patients, there were no significant differences in main outcomes. New-onset atrial fibrillation, major bleeding, and acute kidney injury occurred less after TAVI; new pacemakers, vascular complications, and paravalvular leak occurred more after TAVI. Conclusion: In lower-risk patients, there was an early mortality reduction with TAVI, but no differences after later follow-up. There was also an early reduction in the composite of death or disabling stroke, with no difference at later follow-up. There were no significant differences for higher-risk patients. Informed therapy decisions may be more dependent on the temporality of events or secondary endpoints than the long-term occurrence of main clinical outcomes. Structured Graphical Abstract: Structured Graphical Abstract Summary of clinical outcomes following TAVI and SAVR, categorized into earlier and later events, and lower- and higher-risk trials.